PENGENDALIAN HAYATI PENYEBAB PENYAKIT REBAH SEMAI Fusarium subglutinans DENGAN Trichoderma harzianum - M. Christita; S. M. Widyastuti; H. Djoyobisono (Center for Forest Biotechnology and Tree Improvement (CFBTI), 2014)
The mortality of pine seedling in nursery was caused by damping off. Damping off disease is caused by soil borne pathogenic fungus Fusarium subglutinans. To get an effective method in controlling the diseases, is important to understand the effectiveness of biocontrol agent Trichoderma harzianum. The purpose of this research was to comprehend the inhibition mechanism of T. harzianum against F. subglutinans and its effectiveness. The research methods include (1) in vitro application of T. harzianum with Green Fluorescent Protein [GFP] using dual culture method, and (2) in planta application by inoculating T. harzianum with GFP four days before F. subglutinans inoculation, inoculating T. harzianum and F. subglutinans at the same time, and inoculating of T. harzianum four days after F. subglutinans inoculation. The results of this research showed that Trichoderma harzianum is effective to inhibit the growth of F. subglutinans in planta. The mechanism of T.harzianum to inhibit the growh of F.subglutinans is by nutrient competition.